CSIG-12. PREX1 LINKS ABERRANT PI 3-KINASE PATHWAY SIGNALING TO MAINTENANCE OF THE NEURAL STEM CELL-LIKE PHENOTYPE OF GLIOBLASTOMA CELLS. (11th November 2019) - Lorimer, Ian; Lavictoire, Sylvie; Jomaa, Danny; Gont, Alex; Jardine, Karen
Abstract: Virtually all primary glioblastomas have aberrant activation of the PI 3-kinase pathway through mutational inactivation of tumour suppressors such as PTEN and/or mutational activation of oncogenes. Most glioblastomas also overexpress the Rac guanine nucleotide exchange factor PREX1, which is activated by PI 3-kinase pathway signaling. To determine the role of PREX1 in mediating the effects of aberrant PI 3-kinase pathway signaling in glioblastoma, we used CRISPR/Cas9 to knockout PREX1 in patient-derived glioblastoma cells cultured under conditions that maintain their neural stem cell-like characteristics. Multiple PREX1-null glioblastoma cell clones showed reduced motility and an altered morphology, with a smaller cell body and multiple neurite-like extensions. They also had increased expression of doublecortin, a marker of committed neurogenic progenitor cells. Analysis of RNA-seq data for transcription factor usage was consistent with the acquisition of an intermediate progenitor-like phenotype in PREX1-null cells, with loss of neural stem cell-associated polycomb repressive complex 2 and DMRTA2 activity and the expression of an EOMES/TBR2 signature characteristic of intermediate progenitors. The reduced motility, altered morphology and increase in doublecortin protein levels could all be reversed by re-expression of PREX1. PREX1-null cells had a reduced ability to phosphorylate and inactivate Lgl1, which is required for the maintenance of neural stem cell-like glioblastoma cell populations in vivo . These data show that PREX1 links aberrant PI 3-kinase signaling to maintenance of the neural stem cell-like phenotype in glioblastoma cells.